Manfaat Emotional Freedom Technique (EFT) Bagi Pasien Dengan Gangguan Kecemasan - Nurmawati S Lataima; Ninuk Dian Kurniawati; Puji Astuti (FORIKES, 2020)
Background: Psychological problems such as anxiety are one of the most common problems in the world. Handling for this anxiety problem is not adequate and requires a lot of money. Psychological intervention is needed to help patients overcome the anxiety they experience. Objective: To outline some of the benefits of the Emotional Freedom Technique (EFT) intervention that can help patients reduce anxiety Method: The database used in this study was Scopus, Google Schoolar and Pubmed was limited to the last 5 years from 2015 to 2020, full text article in English. The keywords used were